DEVELOPMENT OF AN INCLUSIVE EDUCATION MODEL BASED ON STAKEHOLDER COLLABORATION IN PANGDI LUHUR ELEMENTARY SCHOOL SEMARANG - Yustina Trihartatik; Bunyamin; Yovitha Yuliejantiningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to develop an Inclusive Education Model Based on Stakeholder Collaboration to strengthen support services for students with special needs in Pangudi Luhur Elementary School Semarang. The research employed a Research and Development (R&D) design referring to the ADDIE model, involving needs analysis, model development, expert validation, and limited implementation. Data were collected through interviews, observations, document analysis, questionnaires, and Focus Group Discussions (FGD) with teachers, parents, school leaders, and special education staff. The expert validation results revealed that the model obtained a score of 91.4% for content validation and 84.3% for media validation, categorizing it as “highly feasible.” During implementation, the model was positively accepted by stakeholders, with an acceptance rate of 84.4% (teachers and school leaders) and 98.2% (parents). The findings conclude that the developed model effectively facilitates structured collaboration and strengthens inclusive practices in elementary schools.